2017
DOI: 10.1016/j.gaitpost.2017.07.108
|View full text |Cite
|
Sign up to set email alerts
|

Foot structure is significantly associated to subtalar joint kinetics and mechanical energetics

Abstract: Please cite this article as: Maharaj Jayishni N, Cresswell Andrew G, Lichtwark Glen A.Foot structure is significantly associated to subtalar joint kinetics and mechanical energetics.Gait and Posture http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The marker set consisted of a four-marker cluster on the thigh and shank segments and anatomical markers placed over the right and left anterior-superior iliac spines; right and left posterior-superior iliac spines; medial and lateral femoral epicondyles; medial and lateral malleoli. For the feet, a multi-segment marker set was used to track the motion of the rear-, mid-and fore-foot segments using 8 anatomical marker locations previously detailed (Leardini et al, 2007;Maharaj et al, 2017b).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The marker set consisted of a four-marker cluster on the thigh and shank segments and anatomical markers placed over the right and left anterior-superior iliac spines; right and left posterior-superior iliac spines; medial and lateral femoral epicondyles; medial and lateral malleoli. For the feet, a multi-segment marker set was used to track the motion of the rear-, mid-and fore-foot segments using 8 anatomical marker locations previously detailed (Leardini et al, 2007;Maharaj et al, 2017b).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The STJ generally functions to maintain frontal plane stability as it absorbs energy during pronation following heel strike and generates power for STJ supination at push-off (Piazza, 2005), with the tibialis posterior (TP) muscle and tendon considered a key muscle in recycling energy across the stance phase (Maharaj et al, 2016). Numerous factors influence the dynamics of the STJ during walking, including the properties of the TP tendinous tissue (Maharaj et al, 2017a), footwear (Maharaj et al, 2018), foot structure (Maharaj et al, 2017b) and gait parameters (Maharaj et al, 2017b;. Deviations in step width may alter frontal plane mechanics and hence the function of its constituting structures such as the STJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deficits in gait and running after an Achilles tendon rupture are for sure due to both changes in muscle strength, ankle range of motion and endurance, but not much is known about what happens to foot posture and foot structure after this injury. It has been reported that different types of foot structure may have an impact on developing overuse injuries in the lower limb in some individuals (10)(11)(12)(13). The medial longitudinal arch in the foot has been described to be low, normal or high and depending on the height, it could cause malalignment such as pes cavus or pes planus (14).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an excessive weight-bearing response of hindfoot valgus may apply mechanical stimulation to posterior tendons and cause further microtrauma [7]. Previous studies have reported that an abnormal total weight-bearing response of the navicular and talus bones, such as increased mobility or changes in the ratios of vertical to medial displacement, are likely associated with injuries [8].…”
Section: Introductionmentioning
confidence: 99%